Double telecom band thermo-optic switch based on dual-line filled photonic liquid crystal fibres. Issue 3 (19th February 2017) - Liu, Xiaoqi; Liu, Yange; Wang, Zhi
ABSTRACT: We demonstrate a thermo-optic switch based on photonic liquid crystal fibres (PLCFs) in which two lines of air hole are selective filled with liquid crystal (LC), with a high extinction ratio of more than 20 dB around 1310 nm and 1550 nm. Only in the range of 2.0°C it can perform a turn off and on operation of transmitted light in the second telecom band around 1550 nm while the first telecom bands around 1310 nm is still on. Due to the splitting of the bandgap, the switching function is achieved in this kind of PLCFs. Before the cleaning point (CP) of LC, a broad bandgap from about 1120 nm to 1320 nm splits into two ones, which are continuing inducing huge bandgap extension to shorter wavelength and longer wavelength after the CP of LC, respectively. Moreover, the temperature responses around the CP of LC is also investigated. Its sensitivity is about −92.32 nm/°C around the CP of LC. Therefore, such kind of selective-filled PLCFs could find potential applications as thermo-optic switch and temperature sensor in the telecom band. GRAPHICAL ABSTRACT: